Domain III of Cry1Ac Is Critical to Binding and Toxicity against Soybean Looper (Chrysodeixis includens) but Not to Velvetbean Caterpillar (Anticarsia gemmatalis) - Rubina Mushtaq; Abdul Rauf Shakoori; Juan Luis Jurat-Fuentes (Toxins, 2018)
Insecticidal proteins Cry1Ac and Cry2Ac7 from the bacterium Bacillus thuringiensis (Bt) belong to the three-domain family of Bt toxins. Commercial transgenic soybean hybrids produce Cry1Ac to control the larvae of the soybean looper (Chrysodeixis includens) and the velvet bean caterpillar (Anticarsia gemmatalis). The specificity of Cry1Ac is determined by loops extending from domain II and regions of domain III in the three-dimensional structure of the toxin. In this study, we constructed a hybrid toxin (H1.2Ac) containing domains I and II of Cry1Ac and domain III of Cry2Ac7, in an attempt to obtain a protein with enhanced toxicity compared to parental toxins. Bioassays with H1.2Ac revealed toxicity against the larvae of A. gemmatalis but not against C. includens. Saturation binding assays with radiolabeled toxins and midgut brush border membrane vesicles demonstrated no specific H1.2Ac binding to C. includens, while binding in A. gemmatalis was specific and saturable. Results from competition binding assays supported the finding that Cry1Ac specificity against A. gemmatalis is mainly dictated by domain II. Taken together, these distinct interactions with binding sites may help explain the differential susceptibility to Cry1Ac in C. includens and A. gemmatalis, and guide the design of improved toxins against soybean pests.